Utility of X-Rays in Scar Examination: A Case Report - Waghmare, Sushim; Bardale, Rajesh; Sonar , Vaibhav (Journal of Indian Academy of Forensic Medicine, 2015)
In Forensic practice scar is utilized for identification purpose. The identification may be of  personal identification or to identify any previous injury. In this case report we are reporting the  radiological findings of the scar and discuss the utility of such technique. A 32 year male accused was  referred by the City Police for examination of scar. Forensic examination of scar provides vital information  like type of injury sustained, type of weapon used and probable age of scar. Along with clinical  examination, radiological evaluation in suspected of cases of firearm may provide valuable clue like old  fractures, deformity, callous formation and firearm residue. If facilities are available like multi-slice spiral  CT scan then radiological evaluation become easier. The advantages of such techniques are  considerable like one can visualize the image in Bone Window and Volume Render Technique format;  one can have three dimensional view and therefore the image can be rotated and visualized in 360  degree. The present case highlights the importance of utilizing the radiological modality while examining  the scar for medico-legal purpose.
Keywords: Identification; Scar; Firearm; X-Ray; Radiology